Regression of left ventricular mass after transcatheter aortic valve implantation. (4th February 2022) - Costa Mauricio, AR; Goncalves, S; Santiago, H; Prata, S; Santos, L; Vaz, R; Ribeiro, F; Almeida, A; Pinto, F
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Regression of left ventricular mass (LVM) after transcatheter aortic valve implantation (TAVI) is an important parameter of left ventricular reverse remodeling and is associated with less hospitalizations 1year after TAVI. The association between LVM índex (LVMi) at 6 months and outcome 1 year after TAVI is unclear. Purpose: Evaluate and compare LVMi, before TAVI and 6 months after, and determine the association between LVMi regression and clinical outcomes at 1-year follow-up. Methods: Retrospective, comparative study in patients with symptomatic severe aortic stenosis with a high operative risk, after TAVI. All patients underwent echocardiographic study before TAVI and 6 months of follow-up, the LVMi (by the Devereux formula) was evaluated. Associations between LVMi regression (percent change between baseline and 6 months after TAVI), rehospitalization rate and death at 1 year of follow-up were examined. Results: We studied 50 patients, 82% with moderade or severe LVMi before TAVI. Comparative analysis between ecocardiography study before and 6 months after TAVI, showed there was statistically significant decrease in LVMi (150, 7 ± 38 g/m2 vs 132 ± 36 g/m2; p = 0.03). LVMi moderate or severe (between 130 and 154 g/m2) at 6 months was associated with biggest hospitalization rate (p = 0, 03).Comparative analysis between regression of LVMi (before and 6 months after TAVI) and death, showed: decrease of 5% and 10% in LVMi was independently associated with death at 1 year (p = 0, 77 vs p = 0, 4). Conclusions: Patients with severe symptomatic aortic stenosis treated with TAVI who had a significant decrease of LVMi after 6 months of follow-up had lower hospitalization rates, but decrease of LVMi is independently associated with death at 1 year of follow-up.